Imprinting Dimples on Narrowly Dispersed Polymeric Spheres by Heterocoagulation between Hard Polymer Particles and Soft Oil Droplets - Kadowaki, Kanji; Ishii, Haruyuki; Nagao, Daisuke; Konno, Mikio (Langmuir, 2016)
Golf ball-like particles having a number of dimples on their spherical surfaces were prepared by a combined method of heterocoagulation between hard polymer particles and soft silicone oil droplets, polymerization of the oil droplets, and dissolution of the polymer particles with tetrahydrofuran. In the heterocoagulation, polystyrene (PSt) particles of three different sizes were employed as hard particles. Distribution of dimples formed with small-sized PSt particles was less homogeneous than that with middle-sized PSt particles (MPS). Narrowly dispersed golf ball-like particles with homogeneously distributed dimples were successfully prepared with a high number ratio of MPS to oil droplets. The employment of large-sized PSt particles in the heterocoagulation decreased the number of PSt particles required for the stabilization of the oil droplets, which created polyhedron-like particles having dimples on their surface. Additional experiments in which polymer particles with different surface affinities to the oil droplets were heterocoagulated with the droplets revealed that a high surface affinity of particles to the droplets could deeply embed the polymer particles into the droplets and form dimples with a low contact angle.